1970
DOI: 10.1111/j.1399-3054.1970.tb08896.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature of the Culture Medium on Growth and Nitrogen Fixation of Inoculated Legumes and Rhizobia

Abstract: Two pea (Pisum sativum L.) cultivars and a kidney bean (Phaseolus vulgaris L.) cultivars were grown in water cultures at different diurnal temperatures (15, 20, 24, 27, 30°C) or at 10°C night temperature combined with various day temperatures (20, 24, 27, 33 or 35°C) in the root medium. The inoculated plants were, more sensitive to the extreme temperatures than the plants supplied with combined nitrogen (KNO3). The middle‐European pea cv. Violetta was adapted to somewhat higher root temperatures than the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1985
1985

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Obviously, more consideration should be given to variations in all these parameters in future studies. Temperature at night may be especially important: very warm temperate nights (18 C) reduce dinitrogen fixation rate in pea (Minchin & Pate, 1974), a crop known to grow well in cool (Roponen, Valle & Attala, 1970), whilst warm tropical nights (24 C) increase overall growth and dinitrogen fixation of soyabean and cowpea (Huxley, Summerfield & Hughes, 1976;Summerfield et ai, 1978a). Schweitzer & Harper (1980) have recently suggested that the release of stored photosynthates to support nodule activity at night is greater when nights are warm.…”
Section: Diurnal Functioning Of Nodules and Rootsmentioning
confidence: 99%
“…Obviously, more consideration should be given to variations in all these parameters in future studies. Temperature at night may be especially important: very warm temperate nights (18 C) reduce dinitrogen fixation rate in pea (Minchin & Pate, 1974), a crop known to grow well in cool (Roponen, Valle & Attala, 1970), whilst warm tropical nights (24 C) increase overall growth and dinitrogen fixation of soyabean and cowpea (Huxley, Summerfield & Hughes, 1976;Summerfield et ai, 1978a). Schweitzer & Harper (1980) have recently suggested that the release of stored photosynthates to support nodule activity at night is greater when nights are warm.…”
Section: Diurnal Functioning Of Nodules and Rootsmentioning
confidence: 99%